(untitled) - Larsen, William J. (New York, 1993)
"Human Embryology" introduces medical students and other health professionals to the basic concepts and principles which underlie the first eight weeks of human development. Each chapter includes full colour illustrations and revision-oriented summary boxes, as well as sections detailing clinical examples relevant to the chapter. These clinical sections should add relevance to the subject and help the reader retain facts.
Keywords: Sinh lý học phôi thai,Embryology, Human